Smallholding farmers wellbeing in ecosystem services area of high food provider in border area of Indonesia - Wahyuni, Etty; Sutrisno, Adi; Santoso, Dwi; Egra, Saat (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2023)
The utilization of wetland areas poses a threat to the wetland ecosystems’s vitality. The Kayan Sembakung Delta in North Kalimantan Province is one of the wetland ecosystems that is widely used by humans for various activities, raising concenrs about its sustainability. This study aims to assess the area’s carrying capacity and environmental capacity as well as the level of welfare of small farmers. The research was conducted in March-June 2020 in Tanjung Buka Village, Tanjung Palas Tengah District, Bulungan Regency, which is part of the Kayan Sembakung Delta area. The study employed an analysis of the carrying capacity of the environment as well as an analysis of the poverty and welfare assessment of farmer households using the Nested Sphere of Poverty (NESP) approach. The results showed that Tanjung Buka Village has an area with a high carrying capacity and environmental capacity as a food provider covering an area of 61,352.12 ha. Small farmers experience subjective and objective welfare in the moderate category. Increasing the welfare of small-scale farmers can be done through efforts such as repairing houses below proper standards, meeting food needs, increasing consumption of protein (meat, eggs, fish), providing clean water, diversifying income sources, ease of access to food. sources of employment, promoting conservation of wood and plant species, securing  land tenure, complying with local regulations, and improving infrastructure JEL Classification A13; B40; B55